2020
DOI: 10.1136/jim-2019-001056
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endotoxemia in Causing Renal Dysfunction in Cirrhosis

Abstract: Renal failure is a challenging problem in patients with cirrhosis since mortality increases with worsening renal function, hence the inclusion of serum creatinine in calculating the Model for End-Stage Liver Disease score for liver transplant evaluation. Among the various causes, infection is the leading etiology of mortality associated with cirrhosis. Bacterial infection frequently precipitates renal failure in patients with cirrhosis with the reported prevalence around 34%. Patients with cirrhosis are at inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…In support of these observations, we have previously reported an improvement of renal function, along with amelioration of systemic hemodynamics, in patients with cirrhosis and ascites after prevention of endotoxemia with rifaximin treatment [ 23 ]. Experimental evidence has also confirmed that LPS may directly impair renal function in cirrhosis [ 24 ] via distortion of glomerular integrity [ 25 ] and renal vasoconstriction [ 26 , 27 ], independently of systemic hemodynamic changes [ 27 ]. On the other hand, it could be hypothesized that differences in renal function might be a potential factor contributing to SIBO in this subgroup [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In support of these observations, we have previously reported an improvement of renal function, along with amelioration of systemic hemodynamics, in patients with cirrhosis and ascites after prevention of endotoxemia with rifaximin treatment [ 23 ]. Experimental evidence has also confirmed that LPS may directly impair renal function in cirrhosis [ 24 ] via distortion of glomerular integrity [ 25 ] and renal vasoconstriction [ 26 , 27 ], independently of systemic hemodynamic changes [ 27 ]. On the other hand, it could be hypothesized that differences in renal function might be a potential factor contributing to SIBO in this subgroup [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the Child–Pugh class of decompensated cirrhosis, urinary lipocalin-2/IL-18 levels increased and GFR decreased significantly [ 30 , 31 , 32 ]. The most common cause for acute on chronic renal dysfunction in cirrhosis is acute tubular necrosis (ATN), which occurs as a complication of sepsis [ 4 , 5 , 9 , 15 , 32 ]. Urine levels of IL-18 and lipocalin-2 from patients with cirrhosis discriminate between those with ATN and other types of kidney impairments [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…NFκB plays a major role in the inflammatory response, and over-activation of NFκB induces the overexpression of TNFα, thus accelerating renal injury [ 4 , 7 , 8 , 13 , 34 ]. In streptozotocin-induced diabetic nephropathy rats, chronic pioglitazone treatment reduced renal NFκB, IL-1β and IL-18 levels, depressed the glomerular mesangial expansion, and decreased serum BUN/creatinine [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HRS is a severe complication of advanced liver cirrhosis with a prevalence between 11% and 20% ( 140 ). The mechanism of HRS is not clear, but it is mainly related to the following two aspects: on the one hand, the production of ascites increases, and the circulating blood volume decreases after decompensation of liver cirrhosis, resulting in prerenal renal failure ( 141 ); on the other hand, the bacterial dysbiosis and the translocation of bacteria and related products after decompensation of liver cirrhosis lead to the endotoxemia, which is closely related to HRS ( 142 , 143 ). Animal model studies have shown that the increased expression of TLR4 in the kidney tissue of cirrhotic rats increases the susceptibility to LPS, then activates the NF-κB pathway, increases the expression of proinflammatory cytokine tumor necrosis factor-α (TNF-α), and renal tubular injury ( 144 ).…”
Section: Liver Cirrhosis-related Complications and Dysbiosismentioning
confidence: 99%